Pengembangan Media Pembelajaran Berbasis Web “Levietech” Dengan Model Pbl Untuk Meningkatkan Hasil Belajar Siswa Pada Elemen Sistem Komputer - Muhammad Irvan Maulana; Rindu Puspita Wibawa (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Computer System learning in Vocational High Schools (SMK), which is often abstract, motivated this research to develop an interactive website-based learning media named "Levietech". This media is integrated with the Problem Based Learning (PBL) model to improve the cognitive learning outcomes of 10th-grade Computer and Network Engineering (TKJ) students at SMKN 1 Sarirejo. This study applied a Research and Development (R&D) approach using the ADDIE method and a One-Group Pretest-Posttest design involving 22 students. The expert validation results showed that the platform was categorized as "Highly Feasible" with an average validation score of 91.70%. In the implementation phase, a significant improvement in cognitive achievement was proven by the surge in the average pre-test score from 50.68 to 83.41 in the post-test, supported by the Paired Sample T-Test results (p < 0.001) and an N-Gain index of 0.66 (Medium category). Furthermore, the practicality evaluation using the User Experience Questionnaire (UEQ) demonstrated a highly "Positive" student perception across all measurement dimensions (scores > 0.8). Students were specifically enthusiastic about the Live Quiz feature within the website, which successfully made the evaluation process much more enjoyable and engaging. Thus, the Levietech learning media is proven to be valid, highly practical, and effective in significantly boosting students' understanding and learning enthusiasm.